An examination of the relationship between negative emotions and family dynamics in individuals with internet addiction - Chen, Yao; Tian, Xiwen; Zhou, Xuhui (Frontiers in Psychiatry, 2025)
BackgroundThis study investigates the characteristics and typologies of family cohesion and adaptability among individuals diagnosed with Internet Addiction Disorder (IAD), and explores the associations between these family dynamics and levels of depression and anxiety. The findings aim to inform the theoretical underpinnings of family-based therapeutic interventions for IAD.MethodsA cross-sectional survey design was adopted, employing four well-validated instruments: the Young Diagnostic Questionnaire for Addiction, the Family Cohesion and Adaptability Scale, the Depression Scale, and the Anxiety Scale. The sample comprised 150 individuals diagnosed with IAD from the outpatient department of the Second People’s Hospital of Hunan Province, and a control group of 150 age- and gender-matched individuals without IAD. Statistical analyses, including independent sample t-tests and Pearson correlation analyses, were conducted using SPSS version 27.0.Results(1) Compared to the control group, individuals with IAD reported significantly lower scores in both actual intimacy and actual adaptability, as well as in ideal adaptability, on the FACES scale (all P < 0.001). Dissatisfaction scores for both intimacy and adaptability were significantly higher in the IAD group (P < 0.002). The predominant family typologies identified in the IAD group were disengaged (49.3%) and rigid (80.0%). (2) Levels of depression and anxiety were significantly elevated in the IAD group compared to the control group (P < 0.001). (3) Actual and ideal scores of family intimacy and adaptability were negatively correlated with depression and anxiety scores in the IAD group (P < 0.05).ConclusionThe findings highlight the necessity of a dual-focused intervention strategy. Preventive programs should prioritize individuals exhibiting lower levels of family cohesion and adaptability, with an emphasis on educating parents about the crucial influence of family dynamics on child development and providing guidance on improving the home environment. Concurrently, attention to the mental health of children is essential. Early identification and intervention for symptoms of depression and anxiety may help prevent the escalation of comorbid conditions such as Internet Addiction Disorder and emotional dysregulation, thereby enhancing the effectiveness of therapeutic outcomes.